Radiation Modeling and Finite Cloud Effects for Atmospheric Dispersion Calculations in Near-field Applications: Modeling of the Full Scale RDD Experiments with Operational Models in Canada, Part II. Issue 5 (May 2016) - Lebel, Luke; Bourgouin, Pierre; Chouhan, Sohan; Ek, Nils; Korolevych, Volodymyr; Malo, Alain; Bensimon, Dov; Erhardt, Lorne
Abstract : Abstract: Three radiological dispersal devices were detonated in 2012 under controlled conditions at Defence Research and Development Canada's Experimental Proving Grounds in Suffield, Alberta. Each device comprised a 35‐GBq source of 140 La. The dataset obtained is used in this study to assess the MLCD, ADDAM, and RIMPUFF atmospheric dispersion models. As a continuation ofLebel et al. (2016), this paper examines different methodologies for making dose estimates with atmospheric dispersion models.